THE COGNITIVE REPRESENTATION OF PHRASEOLOGICAL UNITS IN THE DOMAIN OF "SCIENCE" IN FRENCH PHRASEOLOGY - Ashurova Rano (Web of Journals Publishing, 2024)
This article provides an in-depth exploration of the cognitive and cultural characteristics of phraseological units (PUs) within the domain of "science" in French phraseology. By integrating insights from cognitive linguistics, phraseology, and cultural studies, the article examines the semantic, grammatical, and etymological aspects of these units. Special attention is given to the role of metaphorical mapping, syntactic rigidity, and cultural alignment in shaping science-related PUs. The findings contribute to a better understanding of how these units reflect epistemological values and cultural narratives embedded in French scientific discourse.